2018
DOI: 10.33338/ef.70036
|View full text |Cite
|
Sign up to set email alerts
|

Effects of constant and fluctuating temperatures on development and reproduction of Megoura crassicauda and Aphis craccivora (Hemiptera: Aphididae)

Abstract: The influence of fluctuating temperatures on the development and fecundity of two aphids, Megoura crassicauda Mordvilko and Aphis craccivora Koch, were determined by collecting life table data at a constant temperature (22 °C) and two fluctuating temperatures (22 ± 3 °C and 22 ± 5 °C). The longevity of M. crassicauda decreased significantly at 22 ± 3 °C and 22 ± 5 °C, while there was no significant difference in the longevity of A. craccivora among the three treatments. The fecundity and intrinsic rate of incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…Compared to the constant temperature treatment, pre-adult development of R. pedestris was similar, but female longevity and oviposition period were significantly longer in fluctuating temperature treatments. These findings are partially consistent with the results of earlier studies on Bicyclus anynana [43], Helicoverpa armigera [44], Tetranychus urticae, Phytoseiulus persimilis, Neoseiulus californicus [45], and Megoura crassicauda and Aphis craccivora [46].…”
Section: Discussionsupporting
confidence: 92%
“…Compared to the constant temperature treatment, pre-adult development of R. pedestris was similar, but female longevity and oviposition period were significantly longer in fluctuating temperature treatments. These findings are partially consistent with the results of earlier studies on Bicyclus anynana [43], Helicoverpa armigera [44], Tetranychus urticae, Phytoseiulus persimilis, Neoseiulus californicus [45], and Megoura crassicauda and Aphis craccivora [46].…”
Section: Discussionsupporting
confidence: 92%
“…However, MT treatments significantly increased the intrinsic rate of increase of R. padi . Similar heat stress responses have been observed in Aphis glycines (Kikuchi et al ., ), Acyrthosiphon gossypii (Gao et al ., ), Megoura crassicauda , and Aphis craccivora (Cheng et al ., ). Extreme temperatures can impair multiple physiological processes in organisms (Ohtaka & Ishikawa, ; Davis et al ., ; Auad et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…The life‐history traits of R. maidis (Kuo et al ., ) and Aphis gossypii (Parajulee, ) were variable at mean temperatures of 10, 15, 20, 25, 30, and 35 °C. In recent years, an increasing number of researchers have found that fluctuating temperature treatments should be considered in evaluating the response of aphids to heat stress (Davis et al ., ; Jeffs & Leather, ; Cheng et al ., ; Gao et al ., ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Numerous studies demonstrate how insect survival, morphology, fecundity, and the development period are affected by temperature fluctuations, either positively or negatively, eventually affecting species interactions and the provision of ecosystem services [30][31][32][33]. For example, Bayu et al [34] showed that the intrinsic rate of population increase in the spider mite Tetranychus urticae was higher under a fluctuating 15 • C (±10 • C) thermal regime, compared to a constant 15 • C, but that the temperature fluctuation was not always favorable for other traits or other regimes.…”
Section: Introductionmentioning
confidence: 99%